2014
DOI: 10.3892/ijo.2014.2751
|View full text |Cite
|
Sign up to set email alerts
|

Protumorigenic role of Timeless in hepatocellular carcinoma

Abstract: Abstract. The mammalian timeless (TIM) protein interacts with proteins of the endogenous clock and essentially contributes to the circadian rhythm. In addition, TIM is involved in maintenance of chromosome integrity, growth control and development. Thus, we hypothesized that TIM may exert a potential protumorigenic function in human hepatocarcinogenesis. TIM was overexpressed in a subset of human HCCs both at the mRNA and the protein level. siRNA-mediated knockdown of TIM reduced cell viability due to the indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
3
27
0
Order By: Relevance
“…3 Additionally, an increasing number of studies have found that Timeless is over-expressed in several tumor types, including lung cancer, breast cancer, hepatocellular cancer, and cervical cancer. 4,[5][6][7][8] Furthermore, aberrant Timeless expression is associated with poor survival in lung cancer, breast cancer, and cervical carcinoma, 4,6,8 indicating that Timeless plays a substantial role in these malignancies. Besides, recent studies have shown that Timeless is involved in the regulation of homologous recombination (HR) and nonehomologous end joining (NHEJ) repair, which are two important methods to repair DNA damage by interacting with poly (ADP-ribose) polymerase-1 (PARP-1).…”
Section: Introductionmentioning
confidence: 99%
“…3 Additionally, an increasing number of studies have found that Timeless is over-expressed in several tumor types, including lung cancer, breast cancer, hepatocellular cancer, and cervical cancer. 4,[5][6][7][8] Furthermore, aberrant Timeless expression is associated with poor survival in lung cancer, breast cancer, and cervical carcinoma, 4,6,8 indicating that Timeless plays a substantial role in these malignancies. Besides, recent studies have shown that Timeless is involved in the regulation of homologous recombination (HR) and nonehomologous end joining (NHEJ) repair, which are two important methods to repair DNA damage by interacting with poly (ADP-ribose) polymerase-1 (PARP-1).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, TIM has been reported to be upregulated in various human tumor types and to be involved in cancer development and progression [10, 11]. In bladder cancer, TIM expression is correlated with risk of progression to muscle-invasive disease [12].…”
Section: Introductionmentioning
confidence: 99%
“…TIM is upregulated in lung cancer, and patients with high TIM expression have a poor prognosis [10]. Knockdown of TIM in hepatocellular carcinoma cells induces apoptosis, arrests cell cycle in the G2 phase, and inhibits cell migration by perturbing the interaction with eukaryotic elongation factor 1A2 (EEF1A2) [11]. Moreover, TIM is upregulated in tissue in metastatic prostate cancer, and TIM knockdown in prostate cancer cell PC3M suppresses cell migration [13].…”
Section: Introductionmentioning
confidence: 99%
“…Rhythmic fluctuations have been identified in hepatic metabolic functions with a 24-h periodicity ( 22 ). Previous studies have demonstrated that liver cancer initiation may be due to alterations in circadian rhythmic genes, including PER3 ( 23 ) and CRY genes, and casein kinases ( 24 ). Additionally, it has been revealed that the dysregulation of metallothionein-1 (MT-1), MT-2 and metal transcription factor-1 are involved in the alterations to circadian rhythms present in liver cancer ( 25 ).…”
Section: Introductionmentioning
confidence: 99%